2020
DOI: 10.1177/1359105319897778
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression and obesity is mediated by weight perception

Abstract: This study investigates whether the association between obesity and depression is mediated by the perception of body weight and verifies the combined effect of being obese and having a self-perception of being fat on depression in a population-based sample of 1238 individuals. Weight perception mediated the association between depression and obesity in 39.3 percent of participants. In stratified analysis, mediation occurred in the following groups: non-single, those with more schooling, non-alcohol abusers, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
2
20
2
1
Order By: Relevance
“…They also found that some groups were more vulnerable: being non-single, having more schooling and not engaging in physical activity. 43 Our data contrasted with different Brazilian studies showing regional heterogeneity. In our study, the association between higher rates of commuting-related physical activity and lifetime history of MDD lost its significance after adjustment.…”
Section: Discussioncontrasting
confidence: 99%
“…They also found that some groups were more vulnerable: being non-single, having more schooling and not engaging in physical activity. 43 Our data contrasted with different Brazilian studies showing regional heterogeneity. In our study, the association between higher rates of commuting-related physical activity and lifetime history of MDD lost its significance after adjustment.…”
Section: Discussioncontrasting
confidence: 99%
“…The themes identified here have all in a broad sense been identified elsewhere among populations with overweight and obesity. The well-reported psychological consequences of overweight largely stem from individuals with overweight themselves (Ciao et al, 2012;Paulitsch et al, 2019;Piana et al, 2013), and repeated research suggests that individuals with overweight not only recognize the physical health consequences associated with excess body weight (Piana et al, 2013;Tinker and Tucker, 1997;Weaver et al, 2008;Winter and Wuppermann, 2014) but also have a tendency to minimize the importance of these (Piana et al, 2013;Weaver et al, 2008;Winter and Wuppermann, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Needless to say, the treatment-seeking participants see obesity as a condition that needs to be changed. This point of view comes from perceived body weight (46), body dissatisfaction (47), and weight bias internalization (48), which are strongly in uenced by media exposure and negative beliefs about obesity in these communities (49). In contrast, since higher socioeconomic groups in developing countries are more likely to be obese, obesity sometimes is regarded as well-being and wealth (50).…”
Section: Discussionmentioning
confidence: 99%